2016
DOI: 10.5812/hepatmon.31245
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Effects of Common Mouthwashes on Candida Strains Colonized in the Oral Cavities of Liver Transplant Recipients in South Iran in 2014

Abstract: Background:Among the opportunistic microorganisms, fungi, particularly Candida, play an important role in the mortality of transplant recipients. Thus, controlling and preventing fungal colonizations in various parts of the body, including the oral cavity, can reduce the possibility of post-transplant invasive fungal infections. This can be done simply by using mouthwashes.Objectives:The current study aimed to determine the prevalence of fungal species of Candida within the oral cavities of liver transplant re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
0
14
1
Order By: Relevance
“…10 Using fluconazole as prophylaxis in all patients may have led to selection pressure and an increased rate of isolation of nonCandida albicans species, which can be fluconazole resistant. 12 In contrast to most studies, Hjortrup and associates reported gram-positive bacteria as the predominant causative agents (67%) in post-LT infection. 13 In our study, the most common grampositive bacteria were Enterococcus species, of which vancomycin-resistant enterococci were the majority (74%), consistent with other reports from Iran.…”
Section: Discussionmentioning
confidence: 82%
“…10 Using fluconazole as prophylaxis in all patients may have led to selection pressure and an increased rate of isolation of nonCandida albicans species, which can be fluconazole resistant. 12 In contrast to most studies, Hjortrup and associates reported gram-positive bacteria as the predominant causative agents (67%) in post-LT infection. 13 In our study, the most common grampositive bacteria were Enterococcus species, of which vancomycin-resistant enterococci were the majority (74%), consistent with other reports from Iran.…”
Section: Discussionmentioning
confidence: 82%
“…Nevertheless, a limitation in our study is the number of representative strains of each species. We have used strains obtained from a kidney transplant recipients cohort previous investigation from our group and the prevalence of C. albicans was higher than the other species, as described everywhere [ 37 , 38 ]. Therefore, for this reason, the number of NCAC strains is lower and definitely may have influenced our results.…”
Section: Resultsmentioning
confidence: 99%
“…Oral candidiasis was diagnosed in 8% of the pediatric patients, and 46.8% of the patients with hematologic disorders were colonized with Candida species (23,24). Candida albicans is the most commonly implicated organism recovered from 60% of dentate patient's mouth over the age of 60 and 50.5% of Candida species isolated from the oral cavity of liver transplant recipients (25)(26)(27). However, other Candida species like C. parapsilosis and C. glabrata may be identified as the cause of infection (28).…”
Section: Discussionmentioning
confidence: 99%